UK podiatrists’ experiences of podiatry services for people living with arthritis: a qualitative investigation - McCulloch, L; Borthwick, A; Redmond, A; Edwards, K; Pinedo-Villanueva, R; Prieto-Alhambra, D; Judge, A; Arden, N; Bowen, C (BioMed Central, 2018)
Background Provision of podiatry services, like other therapies in the UK, is an area that lacks guidance by the National Institute for Health and Care Excellence. Many individuals living with arthritis in the UK are not eligible to access NHS podiatry services. The primary aim of this investigation was to understand the views of podiatry clinicians on their experiences of referral, access, provision and treatment for foot problems for patients who have arthritis. Methods Focus groups were undertaken to explore, in-depth, individual views of podiatrists working in the UK to gain feedback on experiences of barriers and facilitators to referral, access, provision and treatment for foot problems for individuals living with arthritis. A purposive sampling strategy was adopted and two, semi-structured, focus group interviews conducted, involving 12 podiatrists from both NHS and independent sectors. To account for geographical variations one focus group took place in each of 2 predetermined ‘zones’ of the UK; Yorkshire and Hampshire. Thematic analysis was employed to identify key meanings and report patterns within the data. Results The key themes derived from the podiatry clinician focus groups suggest a variety of factors influencing demand for, and burden of, foot pain within the UK. Participants expressed frustration on having a service that accepts and treats patients according to their condition, rather than their complaint. Additionally, concern was conveyed over variations in the understanding of stakeholders’ views of what podiatry is and what podiatrists aim to achieve for patients. Conclusion Podiatrists interviewed believed that many individuals living with arthritis in the UK are not eligible to access NHS podiatry services and that this may be, in part, due to confusion over what is known about podiatry and access criteria. Essentially, podiatrists interviewed called for a timely renaissance of current systems, to newer models of care that meet the foot care needs of individual patients’ circumstances and incorporate national multi-disciplinary guidance. Through this project, we have formulated key recommendations that are directed towards improving what other stakeholders (including GPs, commissioners and users of podiatry services) know about the effectiveness of podiatry and also to futureproof the profession of podiatry.